Determinant of customer loyalty’s influence: a study case of Bluebird Taxi - Afner Khrisna Hidayat; Filda Rahmiati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Transportation services have undergone many changes and improvements over time, particularly in the digital era, making it easier for users to obtain transportation services at any time and from any location. As a result, business actors in the transportation sector are competing to provide attractive transportation services and offers to meet the community's mobility needs, so that users are satisfied and loyal to their services. This study aims to evaluate the influence of Service Quality, Service Benefit, System Quality, and Price on Customer Loyalty of Blue Bird taxi as a prominent taxi provider in Indonesia. The methodology used in this study is the Quantitative method and the statistical analysis was performed using the software of SPSS (Statistical Package for Social Science ) version 25.0. The research population for this study is the user of Blue Bird taxi in the last 5 years and has gained data from 154 respondents in total through a form questionnaire. The results of this study show that Service Quality and Service Benefits do not influence Customer Loyalty to Blue Bird taxi significantly. Meanwhile, the other variable of System Quality and Price has influenced the Customer Loyalty of Blue Bird taxi. Moreover, this study also shows that Service Quality, Service Benefit, System Quality, and Price have a simultaneous influence on Customer Loyalty to Bluebird.